Aplikasi Mobile Doa dan Dzikir Berbasis Android 2.2 - Lely Prananingrum; Budi Utami Fahnun (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
Every Muslim prayer and dhikr is a liability and needs to be performed. In practice prayer andremembrance can not be done just in the middle of dense activity and high mobility. With the mobiletechnology user application would be more practical if we read it through mobile media. We no longer needto carry a book everywhere. Reading and listening will be easier because we can read and listen to it viamobile phone anytime and anywhere. That's what the author wants to make the application of prayer anddhikr is android based.With the above problems, the authors intend to design an application that can allow users to getprayer and dhikr information quickly and accurately by using mobile devices based on Android. In thispaper the authors discuss how to design applications using SDLC (System Development Lie Cycle) with awaterfall process model.Keywords: Android, Mobile Application, Prayer and Dhikr, Mobile